2017
DOI: 10.1002/pts.2330
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of cushion properties of a 3D printed thermoplastic polyurethane Kelvin foam

Abstract: The cells in conventional packaging foams have random size and orientation, and the energyabsorbing behaviour of these foams is determined by the collective contribution of different sizes of cells. In contrast to the random nature of stochastic foams, 3D printing technologies allow engineers to design and produce foams having engineered cellular structures. In this study, engineered cellular structures based on the classic Kelvin 1887 model were 3D printed in 30 × 30 × 30 mm thermoplastic polyurethane cubes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 18 publications
(54 reference statements)
1
47
0
Order By: Relevance
“…Since additive manufacturing is being widely used, the PUFs industry must pay attention to this technology to avoid becoming obsolete. In fact, Changfeng Ge et al [ 27 ] have already reported a preliminary study of the properties of a 3D printed PUF and stated that these materials presented similar resilience properties to bulk rubber, but its density was four times lower than that of rubber. Moreover, this technology allows the possibility of printing products in customized sizes and shapes, which offers engineers an opportunity to design new cushion materials that are tailored for packaging applications.…”
Section: Polyurethane Foamsmentioning
confidence: 99%
“…Since additive manufacturing is being widely used, the PUFs industry must pay attention to this technology to avoid becoming obsolete. In fact, Changfeng Ge et al [ 27 ] have already reported a preliminary study of the properties of a 3D printed PUF and stated that these materials presented similar resilience properties to bulk rubber, but its density was four times lower than that of rubber. Moreover, this technology allows the possibility of printing products in customized sizes and shapes, which offers engineers an opportunity to design new cushion materials that are tailored for packaging applications.…”
Section: Polyurethane Foamsmentioning
confidence: 99%
“…The polyhedron which is used as the base cell of the Kelvin foam is the tetrakaidecahedron consisting of 14 slightly curved faces and 24 vertices. 21,[78][79][80] In Simone et al (1998) 60 the analytical descriptions for the closed cell tetrakaidecahedral foam for calculating the Young's modulus and peak stress are given. It is important to note that the thickness is assumed to be constant in the whole foam cell wall.…”
Section: Octahedral Cell Model 74mentioning
confidence: 99%
“…When the foam is compressed to maximum σmax , the energy density e load can be obtained by calculating the area of the stress‐strain as illustrated in Figure . The e load in Figure is represented as the e indicated in Equations through …”
Section: Development Of Cushion Curvementioning
confidence: 99%
“…For example, the C* of expanded polyethylene (EPE) foam materials range from 3.95 to 4.70; the C* of the EPS is 2.50 . And if the cushioning materials is theoretically described with tangent elasticity, hyperbolic tangent elasticity, and linear elasticity, the C* are 2, 3.9, and 1, respectively …”
Section: Development Of Cushion Curvementioning
confidence: 99%